(untitled) (Anclajes, 2020)
By focusing on Argentine writer Manuel Ugarte’s 1911-1913 lecture tour, this article explores the reconversion of Latin Americanism from a spiritualist and literature discourse to a performative and spectacular practice, articulated by a militant intellectual for a multitude that listens and watches. In particular, it focuses on the role Ugarte gives to the telegram, a product of undersea cable communication technologies, in the organization of student and worker collectives, meant to reconstitute the idea of Latin America through activism. El destino de un continente (1923), the book in which Ugarte narrates his tour, is read here as a performative archive that allows to formulate an alternative genealogy of Latin Americanism rooted in notions of the body, technology, and affect.